2009
DOI: 10.1136/gut.2009.188367
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the liver progenitor cell niche in liver diseases: potential involvement of Wnt and Notch signalling

Abstract: A distinct pattern of HPC surface markers was found between acute and chronic liver diseases. Similar to what is known from animal experiments, strong evidence has been found signifying the role of Wnt signalling in proliferation of human HPCs whereas Notch signalling is involved in biliary differentiation. These pathways can be targeted in future therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
208
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(225 citation statements)
references
References 62 publications
14
208
1
2
Order By: Relevance
“…Hypothetically, HCC might develope only from a small number of cells present in the cirrhotic liver, which are characterized by specific stem cell characteristics, such as suggested for the oval cell population. 48,49 In summary, the simultaneous analysis of about equal numbers of normal liver, cirrhotic liver and HCC with a novel, global tool assessing CpG islands allowed the delineation of distinct methylation patterns in cirrhotic and malignantly transformed liver suggesting a specific methylation biology of these processes. The origin of methylation stemness in HCC cannot, however, be finally clarified by our study-to pinpoint the clonal origins, further studies using HCC arising in noncirrhotic livers and the analysis of microdissected oval cell subpopulations will be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetically, HCC might develope only from a small number of cells present in the cirrhotic liver, which are characterized by specific stem cell characteristics, such as suggested for the oval cell population. 48,49 In summary, the simultaneous analysis of about equal numbers of normal liver, cirrhotic liver and HCC with a novel, global tool assessing CpG islands allowed the delineation of distinct methylation patterns in cirrhotic and malignantly transformed liver suggesting a specific methylation biology of these processes. The origin of methylation stemness in HCC cannot, however, be finally clarified by our study-to pinpoint the clonal origins, further studies using HCC arising in noncirrhotic livers and the analysis of microdissected oval cell subpopulations will be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al showed significant survival differences between HCC patients with a hepatocyte-like phenotype and a hepatoblast-like phenotype [70,71] . Other studies suggest that HCC positive for Keratin 19 (KRT19), which is a progenitor cell marker, have a higher rate of recurrence after resection or transplantation [72][73][74] .…”
Section: Hepatocarcinogenesis and Tumormicroenviromentmentioning
confidence: 99%
“…Wnt/␤-catenin has a role in patterning the foregut endoderm from which the liver arises, in producing a gradient involved in hepatic induction that patterns the gut along the anterior-posterior axis, and in promoting expansion of bipotential hepatoblasts that form the nascent liver bud (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The importance of the Wnt/␤-catenin pathway in liver persists throughout the life of an adult organism, as it plays roles in zonal metabolism (13)(14)(15)(16), hepatic progenitor maintenance (17)(18)(19)(20)(21), and liver regeneration (22)(23)(24)(25)(26)(27), and its dysregulation is observed in many liver cancers (28).…”
mentioning
confidence: 99%